MENINGKATKAN PENJUALAN UMKM MELALUI PROMOSI DIGITAL MARKETING, INOVASI PRODUK, DAN PENGELOLAAN LAPORAN KEUANGAN PADA UMKM TAHU PAK EMAN DI DESA CIGOMBONG - Helda Pebrasari; Karimatun Nisa; Sri Harini; Tini Kartini; Nida Khoerun Nisa; Muhammad Rizqy Adzlan Junaedi; Adelita Safira; Rifki Septian Eka Putra (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
UMKM are businesses or businesses owned by individuals or business entities that meet the criteria for micro businesses. As regulated in statutory regulation no. 20 of 2008, according to the definition of UMKM, the criteria for UMKM are differentiated individually, including micro businesses, small businesses and medium businesses. However, UMKM in Cigombong Village are experiencing many problems, such as Cigombong Village MSMEs still don't understand digital marketing, how to make attractive logo designs, banners and packaging, how to promote a wider market, how to keep UMKM products attractive (Innovation). Based on the results of the discussion, Tahu Pak Eman UMKM were selected and for the digital marketing work program for all Cigombong Village UMKM. Activities are carried out through the Thematic Real Work Lecture (KKN-T) program, which is a community service-based activity to increase student empathy for the conditions of society and the environment. The 2023 Thematic KKN will be implemented in Cigombong Village, Cigombong District using service methods such as counseling, training and group mentoring. The results show that there is a positive response and high active participation from the community, including designing logos and banners, taking part in the Digital Marketing Training program, training in making innovative tofu dregs into tofu dregs chips, understanding how to improve good financial reports.